Rally Sport Racing Game: CodeName Space Racer - An evaluation of techniques used when developing a marketable 3D game - Lemon, Maria; Örnvall, Gustav; Axelsson, Daniel; Pettersson, Markus; Gjälby, Ludvig; Råman, Joakim; Almlöf, Sebastian (My University, 2012)
In this thesis, various modern game programming and modeling techniques are presented, with a focus on algorithms for graphical effects. A few of those techniques have then been selected and implemented in a graphics-intensive racing game set in an open space environment. The game is developed from the ground up in C# with the XNA 4.0 framework. The performance of the implemented techniques has then been evaluated. For the graphics, implementations of deferred rendering, Phong-shading, environment maps, exponential shadow maps, screen-space ambient occlusion, lens flares, bloom, depth of field and motion blur have been included in the game. A physics engine has been developed from the ground up using a numerical implementation of Newtonian mechanics with Euler-forward integration and a multi-phase collision detection system using Sweep-and-prune and OBB-intersection algorithms. Network play allowing games over LAN or the Internet has been included with the help of the Lidgren-network-gen3 library.
Keywords: Datavetenskap (datalogi); Computer Science